Keputusan Investasi Keuangan dan Fear of Missing Out Sebagai Variabel Mediasi pada Mahasiswa UPN Veteran Jawa Timur - Phung, Cavin Kleinsteuber; Nur, Dhani Ichsanuddin (Universitas Batanghari, 2024)
Over the past five years, the percentage growth of investors in Surabaya has experienced extreme fluctuations due to rapid advancements in information development. Easy access to information through social media and the surrounding environment has a significant potential to influence an individual's investment decisions. According to behavioral finance theory, psychological factors influence investment decisions, where information from the environment can lead to herding behavior, while information from social media can drive impulsive investment decisions. This research was conducted on students of UPN Veteran Jawa Timur with a total of 100 respondents. Data analysis used the SEM PLS method. The analysis results show that herding factors and social media contribute to impact on investment decisions. Additionally, the fear of missing out (FoMO) proves to be an influential mediator between social media and investment decisions. These findings underscore the importance of understanding psychological factors in investment decision-making in the digital era.